Why do trade finance gaps persist: Does it matter for trade and development? - Marc Auboin; Alisa DiCaprio (World Trade Organization (WTO), 2016)
Trade finance shortfalls now appear regularly. Does this matter for trade expansion and economic development in developing countries? Global trade finance has resumed following the 2009 global financial crisis. However, the pattern of recovery has been uneven across countries and categories of firms. The recovery has been robust for the main routes of trade and for large trading companies. By contrast, access to trade finance remains costly and scarce in countries which have the strongest potential for trade expansion. The policy response to this problem depends on whether this represents a market failure, or a new global equilibrium. We introduce new data from a global survey of firms to argue that real shortfalls are exacerbated by perception gaps in a way that has enabled market failures to persist. This has troubling implications most directly through its effect on the ability for small firms to benefit from the reallocation of production and investment within global supply chains.
Keywords: F13; F34; F36; O19; G21; G32; 330; international financial institutions; coherence; G-20; financial crisis; trade and development; trade finance; economic development